46, XY Disorder of Sexual Development with Ambiguous Female External Genitalia: A Case Report - Sah, Anil Kumar; Maharjan, Bipin; Adhikari, Mahesh Bahadur; Baral, Suman; Giri, Mimi (Journal of Advances in Internal Medicine, 2021)
Disorder of Sexual Development (DSD) is a group of congenital conditions with atypical development of sex at chromosomal, gonadal or anatomic level. Genetic males with DSD (46 XY DSD) can present with female external genital phenotype, ambiguous, or a micropenis. It is caused by incomplete intrauterine masculinization with or without the presence of Müllerian structures. It results either from decreased synthesis of testosterone or DHT or from impairment of androgen action. Herein, we report a case of a 13-year child raised as female with hoarseness of voice and gradual enlargement of clitoris with hormonal assessment not suggestive of either 5 Alfa Reductase deficiency, Congenital Adrenal Insufficiency Syndrome or 17β-Hydroxysteroid Dehydrogenase deficiency